Glucose 6-phosphate dehydrogenase deficient subjects may be better “storers” than donors of red blood cells - Tzounakas, Vassilis L.; Kriebardis, Anastasios G.; Georgatzakou, Hara T.; Foudoulaki-Paparizos, Leontini E.; Dzieciatkowska, Monika; Wither, Matthew J.; Nemkov, Travis; Hansen, Kirk C.; Papassideri, Issidora S.; D’Alessandro, Angelo; Antonelou, Marianna H. (Free radical biology & medicine, 2016)
Storage of packed red blood cells (RBCs) is associated with progressive accumulation of lesions, mostly triggered by energy and oxidative stresses, which potentially compromise the effectiveness of the transfusion therapy. Concerns arise as to whether glucose 6-phosphate dehydrogenase deficient subjects (G6PD−), ~5% of the population in the Mediterranean area, should be accepted as routine donors in the light of the increased oxidative stress their RBCs suffer from. To address this question, we first performed morphology (scanning electron microscopy), physiology and omics (proteomics and metabolomics) analyses on stored RBCs from healthy or G6PD− donors. We then used an in vitro model of transfusion to simulate transfusion outcomes involving G6PD− donors or recipients, by reconstituting G6PD− stored or fresh blood with fresh or stored blood from healthy volunteers, respectively, at body temperature. We found that G6PD− cells store well in relation to energy, calcium and morphology related parameters, though at the expenses of a compromised anti-oxidant system. Additional stimuli, mimicking post-transfusion conditions (37°C, reconstitution with fresh healthy blood, incubation with oxidants) promoted hemolysis and oxidative lesions in stored G6PD− cells in comparison to controls. On the other hand, stored healthy RBC units showed better oxidative parameters and lower removal signaling when reconstituted with G6PD− fresh blood compared to control. Although the measured parameters of stored RBCs from the G6PD deficient donors appeared to be acceptable, the results from the in vitro model of transfusion suggest that G6PD− RBCs could be more susceptible to hemolysis and oxidative stresses post-transfusion. On the other hand, their chronic exposure to oxidative stress might make them good recipients, as they better tolerate exposure to oxidatively damaged long stored healthy RBCs. [Display omitted] •Red blood cells donated by G6PD-deficient donors store well compared to control cells.•To simulate transfusion outcomes an in vitro model of transfusion was used showing that.•G6PD− cells could be susceptible to hemolysis and oxidative stress post-transfusion.•Recipient G6PD− plasma better tolerates exposure to long stored healthy RBCs.